Analysis of Christian-Muslim perceptions in Nakuru Municipality, Nakuru County, Kenya - Muthoni Macharia, Esther; Onyancha, Boaz; A Wario, Halkano (IJRDO - Journal of Social Science and Humanities Research, 2017)
Christians and Muslims relationship has had differing perceptions that have created a barrier over centuries to date. These perceptions have not been subjected to investigation and analysis in Nakuru Municipality. Numerous instances have occurred that have left the perceptions of either religion somewhat indifferent on the intentions of the other. Terror attacks and radicalisations in various areas have left many suffering from the loss of loved ones, property and eventually causing negative perceptions between the two. This study investigated and analyzed perceptions via social-theological approaches and textual sources, of the fluid relationships between Christians and Muslims within Nakuru Municipality. The study established that divergences between the two religions outweigh the convergences which cause negative perceptions. The study thus recommends concerted effort from the government, religious leaders and the community to develop joint action plans for tackling and eliminate causes ofnegative perceptions.